Penerapan Metode Finger Painting untuk Mengembangkan Kreativitas Seni Rupa pada Anak Usia Dini di TK Pertiwi 14.06.03 Setrojenar Buluspesantren Kebumen - Khasanah, Nurul; Mulyani, Novi (Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
Application Of The Finger Painting Method To DevelopArt Creativity In Early Children At Pertiwi Tk 14.06.03 Setrojenar Buluspessantren Kebumen.In applying the fingerpainting method to develop artistic creativity in children. Need a way so that children feel they have the ability to be creative as they wish. By implementing this strategy, researchers must use methods that can make children feel curious and challenged with the methods that researchers apply. This research used descriptive qualitative research method. The research location is Pertiwi Kindergarten 14.06.03 Setrojenar Village, Buluspesantren District.With the research subjects B2 grade children, teachers, and school principals. The results of the research on the application of the finger painting method to develop creativity in early childhood art in TK Pertiwi 14.06.03 Setrojenar Buluspesantren that is application of finger painting method in developing visual arts creativity for early childhood in TK Pertiwi 14.06.03. Setrojenar Bulus Pesantren Kebumen has increase and the application of the finger painting method in developing artistic creativity in early childhood at Pertiwi Kindergarten 14.06.03. Setrojenar Bulus Pesantren Kebumen has increased.